Antibacterial Activity of the Endophytic Fungus Fusarium solani Isolated from the Stem of Bauhinia fulva Blume Against Staphylococcus aureus and Escherichia coli - Sari Purbaya; Yenny Febriani Yun; Dara Santika; Yosephine Liliana Intan Danar Saputri; Fitria Rahma Dewi; Riana Zevanisa Arsyi; Dayu Yunita; Fahriani Istiqomah; Siska Elisahbet Sinaga (Jurnal Kartika Kimia, 2026)
Endophytic fungi are microorganisms that live within plant tissues and are capable of producing secondary metabolites with potential antibacterial, antifungal, and anticancer activities. This study aimed to isolate, identify, and evaluate the antibacterial activity of endophytic fungi from the stem of Bauhinia fulva Blume through isolation, morphological identification, fermentation, ethyl acetate extraction, phytochemical screening, and antibacterial testing using the disk diffusion method. The results showed that the isolated endophytic fungus was identified as Fusarium solani, producing 1.4095 g of ethyl acetate extract. Phytochemical screening revealed the presence of alkaloids, flavonoids, quinones, and triterpenoids/steroids. The ethyl acetate extract of F. solani exhibited antibacterial activity against Staphylococcus aureus with a maximum inhibition zone of 20.85 mm and lower activity against Escherichia coli with a maximum inhibition zone of 5.56 mm, indicating its potential as a natural source of antibacterial compounds.